(untitled) (Simbiótica. Revista Eletrônica, 2025)
This article analyzes the perceptions of secondary school students in the City of Buenos Aires regarding the ways in which political issues are addressed in secondary schools, both in specific subjects (such as History and Citizenship) and in specific educational mechanisms, programs, and spaces such as institutional workshops. Based on the fieldwork conducted, it is possible to observe more than the formation of groups aligned with sectors or expressions of the new right, the hidden emergence of a covert polarization. This polarization is expressed through minor comments, derogatory references, and different youth positions regarding school proposals. In the article, we present two aspects. On the one hand, we trace the different proposals, identify who proposes them, and the types of activities carried out. On the other hand, we identify four types of positions regarding the proposals put forward by institutions: those who are uncomfortable with the teachers’ positions; others who are nonconformist regarding the proposed activities and the teaching method; those who are empathetic/convinced by the actions; and those who are adaptive (those who adapt to the proposal in order to internalize it, considering it part of the school curriculum to be incorporated). Through this prism, it is possible to explore the characteristics of political polarization in secondary schools